Desain pembelajaran materi barisan aritmatika dengan menggunakan pendekatan PMRI pada konteks stadion gelora sriwijaya - Fatimah Azzahroh; Zulkardi Zulkardi; Ely Susanti; Meryansumayeka Meryansumayeka (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2026)
Arithmetic sequences are an important topic in mathematics that requires conceptual understanding. However, in classroom practice, this material is often taught without meaningful real-world contexts, leading students to memorize formulas rather than understand underlying concepts. Therefore, this study aimed to design arithmetic sequence learning using the PMRI approach in the context of the Gelora Sriwijaya Stadium. This study employed qualitative design research consisting of three stages: preliminary design, design experiment (pilot and teaching experiment), and retrospective analysis. The participants were 34 eleventh-grade students at SMA Negeri 12 Palembang, South Sumatra, Indonesia. Data were collected through classroom observations, students’ activity sheets (LKPD), and semi-structured interviews, and analyzed descriptively by comparing the initial Hypothetical Learning Trajectory (HLT) with the actual learning trajectory. The findings show that the stadium context supported students in progressively constructing the concept of arithmetic sequences, moving from concrete representations of seating arrangements to identifying constant differences and formulating the nth-term expression through guided reinvention. The activities promoted self-generated models that bridged informal reasoning and formal mathematical representation. This research produced learning design for arithmetic sequence material based on real contexts, which serves as an alternative for teachers in implementing PMRI.